The Utilization Of Digital Literacy Resources By The Teachers In The Selected High Schools In Sumbawa - Saqiran, M. Ilmi; Waluyo, Untung; Soepriyanti, Henny; Susanti, Ni Wayan Mira (Journal of Classroom Action Research, 2025)
This study aims to examine the utilization of digital literacy resources by teachers in two selected schools in Sumbawa, representing urban and rural areas, by exploring the types of digital literacy resources used, teachers' preferences, and the reasons behind their choices. Grounded in the Technology Acceptance Model (TAM) by Fred Davis, which suggests that teachers tend to prioritize Perceived Usefulness (PU) over Perceived Ease of Use (PEOU). This study employs a qualitative method with a case study design. Data collection involved triangulation techniques, including interviews, observations, and document analysis, to ensure data accuracy and reduce bias. Thematic analysis was used to analyze the data. The findings reveal that Davis's theory applies only in specific contexts. The teachers in the urban school were found to prioritize PU over PEOU, utilizing a variety of digital literacy resources, although some demonstrated limited use due to age and technology stuttering. Conversely, the teachers in the rural school prioritized PEOU over PU due to a lack of training, the absence of integration policies, and limited initiatives to incorporate digital literacy resources into teaching.